Studi Pemikiran Imam Az-Zarnuji dalam Membentuk Kepribadian Ikhlas Mengajar - Muhammad Farhat Hasan; Miftahus Surur; Miftahur Rohman (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2025)
This study aims to examine the thoughts of Imam Az-Zarnuji in shaping the sincere personality of teachers, based on his monumental work Ta'lim al-Muta'allim Thariq at-Ta'allum. In the context of modern education, which often falls into materialistic orientation, Az-Zarnuji's perspective offers profound spiritual values, particularly the importance of sincerity as the core foundation of an educator. This research employs a descriptive qualitative method using a library research approach. The data were analyzed through content analysis and reflective thinking techniques. The findings reveal that Az-Zarnuji emphasizes the importance of correct intention, trust in God (tawakkal), self-restraint (wara’), and proper manners in both learning and teaching. Sincerity, according to him, is not merely an initial intention but an ongoing inner state that must be continuously maintained throughout the teaching process. A sincere teacher’s personality is reflected through patience, humility, responsibility, and the blessings of knowledge. These findings are highly relevant to contemporary Islamic education, especially in PGMI (Education for Teachers of Islamic Elementary Schools), in developing educators who are not only academically competent but also spiritually and morally upright.